Social entrepreneurship research: Intellectual structures and future perspectives - Cardella, G. M. (2021)
Social entrepreneurship (SE) is an emerging research field that has received much scholarly attention in recent years. Given the global scope of this attention, this review explores the existing scientific literature on social entrepreneurship to contribute to a systematization of the research field. Based on the publications in Web of Science and Scopus, a total of 1425 scientific articles were analyzed. We used the bibliometric method to describe the evolution of social entrepreneurship research (e.g., evaluation by years, authors, scientific journal articles, and countries in the SE literature that have had the greatest impact in terms of production). In addition, we used the mapping of knowledge networks through the citations and co-citations analysis to identify schools of thought. A keyword co-occurrence analysis was performed to detect key research topics over the years. The results show that, although the research is still in a nascent phase, it has a multidisciplinary character. Furthermore, social entrepreneurship appears to be a concept closely linked to three schools of thought: commercial entrepreneurship, sustainable entrepreneurship, and social innovation. The keywords analysis allowed us to isolate the constructs that the literature has considered antecedents (e.g., socio-psychological factors) and accelerators (e.g., education, network, culture, and gender) to the development of social entrepreneurial intention. We will further discuss the ways researchers can explore this research field and contribute to the global literature.